Islamic Education Reform from the Muhammadiyah Perspective - Devy Habibi Muhammad; Romelah; Moh. Nurhakim (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to find out the philosophy of Muhammadiyah education, as well as to find out the dynamics of the Muhammadiyah education movement. Muhammadiyah was born in 1912M or 1330H because society had many complex problems. One of the problems is that the state of education is getting worse and needs to be developed. This is what encouraged the birth of Muhammadiyah. Likewise, the high level of poverty made this nation appear to be neglected by the colonial authorities, namely the Dutch East Indies. This research uses a descriptive qualitative research approach. This research shows that Muhammadiyah's educational reform was driven by the ideas and strenuous efforts of its founder, K.H Ahmad Dahlan, who prioritized education. Ahmad Dahlan promotes renewal through education focusing on ijtihad, rejection of taqlid, and understanding the Koran and Sunnah. It integrates religious and general knowledge to strengthen faith and civilization in educational institutions. Muhammadiyah formulated an educational philosophy emphasizing the formation of an environment to develop as an individual aware of Allah SWT. and able to master science, technology and art. Muhammadiyah, as an Islamic organization, continues to strive to improve the quality of education through its institutions. Despite challenges and difficulties, the existing management approach has encouraged positive competition among Muhammadiyah educational institutions. However, an in-depth evaluation is needed to improve the overall quality of Muhammadiyah education.